Continuous Flow Synthesis of Cd1‐xZnxS and CdS/ZnS Core/Shell Semiconductor Nanoparticles by MicroJet Reactor Technology. Issue 12 (1st December 2022) - Hiemer, Julia; Stöwe, Klaus
Abstract: From aqueous precursor solutions of metal salts and sodium sulfide using MicroJet Reactor (MJR) technology Cd1‐x Znx S and CdS/ZnS core/shell semiconductor nanoparticles were synthesized. The MJR approach represents an automated, continuous, flexible and scalable route for nanoparticle synthesis, providing a tight control over process parameters and thus simple size, shape and composition control. Since particle sizes below the excitonic Bohr radius were obtained by MJR, the nanoparticulate materials exhibit quantum confinement effects. By varying the precursor ratio the band gap of Cd1‐x Znx S Quantum Dots (QDs) could be targeted from 3.1 to 3.6 eV. CdS/ZnS core/shell QDs were prepared by enclosing CdS particles from MJR with ZnS produced by thermal decomposition of a Zn‐MPA complex. Adjustment of the shell thickness increased the photoluminescence intensity by 43 %. Synthesis of ternary sulfides in the form of core/shell particles broadens the spectrum of materials accessible by MJR and demonstrates the extraordinary flexibility of the technology. Abstract : The flexible and scalable continuous MicroJet Reactor technology was successfully used for the synthesis of ternary metal sulfide quantum dots with compositionally tuned optical properties and complex structures in form of core/shell particles.